Learning Strategies that Predict Success in Overcoming English Language Learning Anxiety - Kristhel Erica F. Gaoat; Marie Jane A. Caligan; Mae Angelica S. Butel; Mee Jay Domingo (Universitas PGRI Semarang, 2022)
This study determined the respondents’ level and causes of their anxiety and the strategies that they use in the context of English language learning (ELL). Also, it identified the language strategies that predict success in overcoming the students’ ELL anxiety. Descriptive-correlational design was used in the study. It involved 171 Grades 9 and 10 indigenous peoples of selected schools in the province of Ilocos Norte. It used two gathering tools: Horowitz et al. (1986) Foreign Language Classroom Anxiety Scale (FLCAS) and Strategy Inventory for Language Learning (SILL) adopted from Oxford (1990). The data gathered from FLCAS made use of descriptive analysis to compute the means and SILL were analysed using averages, percentages and ranks. Pearson r and multiple regression analysis were used to determine the language strategies that could predict respondents’ language learning anxiety and language strategies.The salient findings are: 1) the selected grades 9 and 10 Indigenous peoples experience moderate level of English language learning anxiety; 2) external factors such as in-class activities and classroom atmosphere are the main causes of language learning anxiety of the respondents; 3) Metacognitive strategy is the commonly used strategy of the selected grades 9 and 10 indigenous peoples followed by social strategy, memory strategy, affective strategy, cognitive strategy, and compensation strategy; and 4) the language learning strategies used by the indigenous peoples are all beneficial in their attempt to improve their proficiency in the language. However, the cognitive and affective strategies are the best among the six.